The Influence of Work Culture and Organizational Commitment on Teacher Performance - Risnah, Risnah; Fitria, Happy; Setiawan, Andi Arif (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
This study aimed at partially and simultaneously identify and analyze the influence of work culture and organizational commitment on the performance of teachers at SD Negeri Sekecamatan Baturaja Timur. This study uses primary data through a total population of 410 people with a sample method, namely a sample representing the total number of teachers at SD Negeri Sekecamatan Baturaja Timur is 202 people. data collection techniques using questionnaires, documentation and observation. The data analysis technique used quantitative descriptive analysis techniques and multiple regression. The results of this study state that 1) there is a significant influence of work culture on the performance of teachers at SD Negeri Sekecamatan Baturaja Timur; 2) there is a significant effect of organizational commitment on the performance of teachers at SD Negeri Sekecamatan Baturaja Timur; 3) there is a significant influence jointly on work culture and organizational commitment to the performance of teachers at SD Negeri Sekecamatan Baturaja Timur.